Toledo Adolescent Relationships Study (TARS): Wave 5, 2011 - Giordano, Peggy C. ([Verlag nicht ermittelbar], 2017)
These data are part of NACJD's Fast Track Release and are distributed as they were received from the data depositor. The files have been zipped by NACJD for release, but not checked or processed except for the removal of direct identifiers. Users should refer to the accompanying readme file for a brief description of the files available with this collection and consult the investigator(s) if further information is needed. This study explores the relationship qualities and the subjective meanings that motivate adolescent behavior. More specifically, this study seeks to examine the nature and meaning of adolescent relationship experiences (e.g., with family, peers, and dating partners) in an effort to discover how experiences associated with age, gender, race, and ethnicity influence the meaning of dating relationships. The study further investigates the relative impact of dating partners and peers on sexual behavior and contraceptive practices, as well as involvement in other problem behaviors that can contribute independently to sexual risk taking. The longitudinal design of the Toledo Adolescent Relationships Study (TARS) includes a schedule of follow-up interviews occurring one, three, and five years after the initial interview. Four prior waves of data have been collected (2001, 2002, 2004, and 2006). Data were collected from adolescent respondents through structured in-home interviews utilizing laptop computers. In addition, the fifth wave, conducted in 2011 when the participants were young adults, builds on prior waves by adding quantitative and qualitative assessments of intimate partner violence (IPV).